RESENSI PUISI BERJUDUL “MELUKISMU” KARYA ACHLUDDIN IBNU ROCHIM - Hakim, Lukman (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2023)
The poem “Melukismu” by Achluddin Ibnu Rochim is a representation of love expressed through the aesthetic language of poetry. This work conveys admiration and devotion toward a beloved figure using artistic metaphors, portraying love as a creative and spiritual force. This study aims to reveal the meaning, symbolism, and poetic structure within the poem using a qualitative-descriptive approach. Theories employed include structuralism (A. Teeuw), semiotics (Roland Barthes), and the psychology of love (Erich Fromm). The analysis shows that love in this poem is not merely emotional affection, but a creative force that gives birth to artistic expression. Symbols such as canvas, color, and words reinforce the idea of transcending personal emotion into an aesthetic creation. This poem demonstrates that language can serve as a medium to subtly and symbolically express the deepest of feelings.